Endothelial MT1‐MMP targeting limits intussusceptive angiogenesis and colitis via TSP1/nitric oxide axis. Issue 2 (3rd December 2019) - Esteban, Sergio; Clemente, Cristina; Koziol, Agnieszka; Gonzalo, Pilar; Rius, Cristina; Martínez, Fernando; Linares, Pablo M; Chaparro, María; Urzainqui, Ana; Andrés, Vicente; Seiki, Motoharu; Gisbert, Javier P; et al.
Abstract: Pathological angiogenesis contributes to cancer progression and chronic inflammatory diseases. In inflammatory bowel disease, the microvasculature expands by intussusceptive angiogenesis (IA), a poorly characterized mechanism involving increased blood flow and splitting of pre‐existing capillaries. In this report, mice lacking the protease MT1‐MMP in endothelial cells (MT1 iΔ EC ) presented limited IA in the capillary plexus of the colon mucosa assessed by 3D imaging during 1% DSS‐induced colitis. This resulted in better tissue perfusion, preserved intestinal morphology, and milder disease activity index. Combined in vivo intravital microscopy and lentiviral rescue experiments with in vitro cell culture demonstrated that MT1‐MMP activity in endothelial cells is required for vasodilation and IA, as well as for nitric oxide production via binding of the C‐terminal fragment of MT1‐MMP substrate thrombospondin‐1 (TSP1) to CD47/αvβ3 integrin. Moreover, TSP1 levels were significantly higher in serum from IBD patients and in vivo administration of an anti‐MT1‐MMP inhibitory antibody or a nonamer peptide spanning the αvβ3 integrin binding site in TSP1 reduced IA during mouse colitis. Our results identify MT1‐MMP as a new actor in inflammatory IA and a promising therapeutic target for inflammatory bowel disease. Synopsis: Inflammatory bowel disease comprising ulcerative colitis and Crohn's disease does not have a universal efficient therapy. This study identifies the molecular axis MT1‐MMP/thrombospondin‐1/αvβ3 integrin/nitric oxide as a target to reduce inflammatory intussusceptive angiogenesis and improve colitis. Early expansion of the capillaries in the intestinal mucosa during colitis was caused by intussusceptive/splitting angiogenesis (IA). Deletion of the protease MT1‐MMP from endothelial cells reduced IA and colitis severity. Thrombospondin‐1 (TSP1) processing by MT1‐MMP promoted nitric oxide production, vasodilation and IA. High levels of TSP1 were found in sera from patients suffering low active IBD. Targeting MT1‐MMP/TSP1/αvβ3 integrin/nitric oxide pathway by monoclonal antibodies or minipump‐delivered peptides decreased IA and ameliorates colitis. Abstract : Inflammatory bowel disease comprising ulcerative colitis and Crohn's disease does not have a universal efficient therapy. This study identifies the molecular axis MT1‐MMP/thrombospondin‐1/αvβ3 integrin/nitric oxide as a target to reduce inflammatory intussusceptive angiogenesis and improve colitis.